Metric properties of functions defined by partial automata - Nekrashevich, V. V.; Oliinyk, A. S.; Sushchanskii, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We characterize natural categories in which morphisms are defined by partial automata of the following three types: asynchronous automata, window automata, and automata synchronous over finite alphabets. We distinguish subcategories whose morphisms are defined by finite automata.